2020
DOI: 10.3390/app10207317
|View full text |Cite
|
Sign up to set email alerts
|

Reverse Electrodialysis: Potential Reduction in Energy and Emissions of Desalination

Abstract: Salinity gradient energy harvesting by reverse electrodialysis (RED) is a promising renewable source to decarbonize desalination. This work surveys the potential reduction in energy consumption and carbon emissions gained from RED integration in 20 medium-to-large-sized seawater reverse osmosis (SWRO) desalination plants spread worldwide. Using the validated RED system’s model from our research group, we quantified the grid mix share of the SWRO plant’s total energy demand and total emissions RED would abate (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…As its name suggests, RED is the opposite process of electrodialysis (ED). So, in RED (Figure 1b), when a low salinity solution, such as river water or wastewater, and a high salinity solution, such as brine, are faced, the difference in concentrations generates ion flux between the different compartments, which generates an electric current between the anode and the cathode [25]. The magnitude of the electric current obtained is dependent on the difference of the concentrations of the input streams and the number of cell pairs (repetitive units) in the stack, among other parameters.…”
Section: Electro-membrane Technologies: Current Status and Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…As its name suggests, RED is the opposite process of electrodialysis (ED). So, in RED (Figure 1b), when a low salinity solution, such as river water or wastewater, and a high salinity solution, such as brine, are faced, the difference in concentrations generates ion flux between the different compartments, which generates an electric current between the anode and the cathode [25]. The magnitude of the electric current obtained is dependent on the difference of the concentrations of the input streams and the number of cell pairs (repetitive units) in the stack, among other parameters.…”
Section: Electro-membrane Technologies: Current Status and Challengesmentioning
confidence: 99%
“…Tristan et al [71] estimated the maximum SGE available in terms of net power density and the net specific energy delivered by a RED system in six SWRO desalination plants distributed worldwide, obtaining net specific energy maximum values in the range of 0.08-0.15 kWh•m −3 of desalted water and net power densities up to 3.7 W•m −2 . Moreover, recent studies [25] concluded that if all the salinity gradient energy is harnessed,~40% of the energy demand of an SWRO facility could be supplied; however, a reduction to the 10% of the supply is estimated due to the energy conversion irreversibility and untapped salinity gradient energy.…”
Section: Alternative A2-salinity Gradient Energy Harvestingmentioning
confidence: 99%
“…Different integration of these pressure driven membrane processes have been applied in a variety of wastewater treatment settings: particularly MF and UF as pretreatment to other unit processes [ 2 ]. Compared to the alternatives of electrodialysis and reverse electrodialysis—which are promising desalination technologies that can transform salinity gradient energy into electricity [ 2 , 3 , 4 ]—electrodialysis shows a relatively higher total organic carbon rejection than nanofiltration [ 3 ] but it is still prone to organic and inorganic fouling. Meanwhile, pretreatment with coagulation can enhance organic removal efficacy by the UF process [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The authors published in 2020 a review evaluating advantages and disadvantages of well-known membrane separation materials based on particle size, usually exposed to a large amount of water, versus dense hydrophobic membranes with targeted transport of contaminants through a selective barrier [ 19 , 20 , 21 ]. Electrodialysis (ED) with porous membrane has shown interesting membrane separation applications [ 22 , 23 ] in terms of valuable compound recovery from wastewater [ 17 , 24 , 25 , 26 ]. However, there are many challenges to overcome for a real full-scale application such as adsorbed pollutants on an ionic membrane, weak separation of macromolecules due to excursive membranes [ 24 ], low productivity and energy demanding, polarisation and fouling phenomena [ 25 ], and complex experimental setup (electrode, cationic and anionic membranes, and elution solution).…”
Section: Introductionmentioning
confidence: 99%